(Un)silencing the voices of the country girls: A journey into twentieth-century Irish girlhood through the fiction of Edna O'Brien - Dunbar, Siobhan Mary (University of Ottawa (Canada), 2008)
Edna O'Brien is a prolific and highly successful contemporary Irish novelist, short story writer, and playwright. Her first six novels were banned in 1960s Ireland and since then, her subversive writing about Irish women's lives has often sparked controversy and debate in and even beyond her Irish homeland. This thesis explores O'Brien's portrayal of rural Irish girlhood in post-Independence, twentieth-century Ireland in the novels The Country Girls (1960), A Pagan Place (1970), the short story collection Returning (1982), as well as the later novel Down by the River (1997). Chapter One delves into the mother-daughter bond in O'Brien's fiction. Chapter Two, in turn, examines the often painful father-daughter relationship Finally, Chapter Three discusses O'Brien's complex portrayal of female sexuality. This study argues that O'Brien constructs powerful and haunting fictional voices of "Irish girlhood" and through them, makes a unique contribution to the Irish Bildungsroman tradition. Her fiction points to some of the immense challenges confronted by young adolescent girls in mid-to-late twentieth-century Ireland, not only in their homes but also within their relationships, schools, and rural communities.
Keywords: Women's Studies.; Literature, English.